ANALISIS STRUKTUR INTERNAL BAHASA PADA LAGU Ã¢â‚¬ËœÃƒâ€šMIYAH MISHRIYYAH Ã¢â‚¬Å“BAHEBBAK YÃƒâ€š BELÃƒâ€šDYÃ¢â‚¬Â - Azimah, Nahdliyyatul; Kusumawati, Endah (Program studi Pendidikan Bahasa Arab UNNES, 2021)
The study aims to analyze the Egyptian colloquial song Ã¢â‚¬Å“Bahebbak YÃ„Â BelÃ„ÂdyÃ¢â‚¬Â in the perspectives of hermeneutics and the internal structures of the language that consist of phonology, morphology, syntax, and semantics. It is a qualitative- descriptive study. The researchers collected data by conducting observation, interview and literature review. The results of the research show that: (1) there are phonemic elements found in the song, which are: changing pronunciation of some letters, prolonging a vowel, tilting, and transmitting specific phonemes, (2) there are morphological elements found in the song that include the forms of past tense, present tense, isim fa'il, and isim maf'ul. Moreover, (3) there are grammatical elements found in the song, which are: the arrangement of the nominative and verbal sentences, and two prefixes of the present tense verb, the uses of the subject, and (Ã™â€¦.....Ã˜Â´) for the prohibition, (4) in the perspective of semantics, there are only lexical and metaphor meanings found in the song. Keywords: Internal Structures of the Language, Egyptian colloquial Song, Bahebbak YÃ„Â BelÃ„Âdy. ØªØ¬Ø±ÙŠØ¯ Ø§Ù„Ø¨ØØ« ØªÙ‡Ø¯Ù Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ ØªØÙ„ÙŠÙ„ Ø§Ù„ØºÙ†Ø§Ø¡ Ø§Ù„Ø¹Ø§Ù…ÙŠØ© ØªØØª Ø§Ù„Ù…ÙˆØ¶ÙˆØ¹